2007
DOI: 10.1111/j.1365-2966.2006.11150.x
|View full text |Cite
|
Sign up to set email alerts
|

Clues for the origin of the fundamental metallicity relations - I. The hierarchical building up of the structure

Abstract: We analyse the evolutionary history of galaxies formed in a hierarchical scenario consistent with the concordance Lambda cold dark matter (ΛCDM) model focusing on the study of the relation between their chemical and dynamical properties. Our simulations consistently describe the formation of the structure and its chemical enrichment within a cosmological context. Our results indicate that the luminosity–metallicity and the stellar mass–metallicity (LZR and MZR) relations are naturally generated in a hierarchic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 47 publications
(97 reference statements)
3
75
2
Order By: Relevance
“…de Rossi, Tissera & Scannapieco (2007), for example, have shown that a correlation between mass and metallicity can arise naturally in a hierarchical scenario solely as a consequence of the regulation of SF by merger events. However, the lack of SN-feedback model prevented de Rossi et al (2007) from reproducing the observed slope of the MZR due to overcooling. According to Köppen, Weidner & Kroupa (2007), the MZR might simply reflect variations in the stellar initial mass function (IMF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…de Rossi, Tissera & Scannapieco (2007), for example, have shown that a correlation between mass and metallicity can arise naturally in a hierarchical scenario solely as a consequence of the regulation of SF by merger events. However, the lack of SN-feedback model prevented de Rossi et al (2007) from reproducing the observed slope of the MZR due to overcooling. According to Köppen, Weidner & Kroupa (2007), the MZR might simply reflect variations in the stellar initial mass function (IMF).…”
Section: Introductionmentioning
confidence: 99%
“…Köppen & Edmunds 1999;Dalcanton, Yoachim & Bernstein 2004;Finlator & Davé 2008;Davé, Finlator & Oppenheimer 2011). de Rossi, Tissera & Scannapieco (2007), for example, have shown that a correlation between mass and metallicity can arise naturally in a hierarchical scenario solely as a consequence of the regulation of SF by merger events. However, the lack of SN-feedback model prevented de Rossi et al (2007) from reproducing the observed slope of the MZR due to overcooling.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, luminosity has been used as substitute of mass because of the difficulty of deriving reliable galaxy masses, yielding to the socalled metallicity-luminosity relation (i.e., Rubin et al 1984;Richer & McCall 1995;Salzer et al 2005), although in recent years mass-metallicity relations are also explored (i.e., Tremonti et al 2004;Kewley & Elisson 2008), and are studied even at high redshifts (i.e., Kobulnicky et al 1999;Pettini et al 2001;Kobulnicky & Kewley 2004;Erb et al 2006;Liang et al 2006). The evolution of such relationships are now predicted by semianalytic models of galaxy formation within the Λ-cold dark matter framework that include chemical hydrodynamic simulations (De Lucia et al 2004;Tissera et al 2005;De Rossi et al 2006;Davé & Oppenheimer 2007). Ironically, today the main problem is not to estimate the mass of a galaxy but its real metallicity, so that different methods involving direct estimates of the oxygen abundance, empirical calibrations using bright emissionline ratios or theoretical methods based on photoionization models yield very different values (i.e., Yin et al 2007;Kewley & Elisson 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The sub-pc wind simulations presented by Creasey, Theuns & Bower (2015) demonstrate that dense galactic discs drive metal-enriched winds, whereas lower density discs drive winds with far lower metallicities. Interestingly, de Rossi et al (2007) showed that a correlation between metallicity and mass naturally arises in a hierarchical framework as a consequence of the regulation of the SFR by merger events, without the necessity of invoking SN-driven outflows. However, without SN feedback, they were not able to reproduce the observed slope of the relation (and neglect of SN feedback also leads to significant overcooling).…”
Section: Introductionmentioning
confidence: 99%
“…Tissera, De Rossi & Scannapieco 2005;Brooks et al 2007;de Rossi, Tissera & Scannapieco 2007;Finlator & Davé 2008;Davé, Finlator & Oppenheimer 2011;Peeples & Shankar 2011;Davé, Finlator & Oppenheimer 2012;Yates, Kauffmann & Guo 2012;Dayal et al 2013;Romeo Velonà et al 2013). The lower metallicity of low-mass galaxies is generally thought to be a result of more efficient star formation driven outflows from shallower potential wells (Larson 1974;Tremonti et al 2004;Dalcanton 2007;Kobayashi, Springel & White 2007).…”
Section: Introductionmentioning
confidence: 99%